A study on improving machining characteristics of electrical discharge machining with modified transistor pulse generator. (1st January 2013) - Muthuramalingam, T.; Mohan, B.
The efficacy of pulse generator in electrical discharge machining is characterised by material removal rate and surface roughness. Due to its low frequency operation, RC relaxation pulse generator could produce lower material removal rate and lower surface roughness than transistor pulse train generator. Since transistor pulse generator could produce larger crater volume throughout the process, it could made higher surface roughness with higher material removal rate. By producing smaller crater volume during finishing stage, surface finish can be improved. The main objective of this study is to improve surface finish by enhancing the process mechanism in thermal erosion process. In the present study, a modified form of the transistor pulse generator approach has been developed. The effects of the pulse generators on the machining characteristics has been experimentally evaluated using Taguchi L9 orthogonal table and analysed in the EDM process. Gap voltage, discharge current and duty factor has been chosen as input variables to evaluate the material removal rate. From the results, it is proved that the modified transistor pulse train generator could produce higher surface finish than existing transistor pulse generator with considerable amount.